Rehabilitation of the Roof Timber Trusses of a Multiuse Pavilion - João H. Negrão (Salehan Institute of Higher Education, 2020)
This paper describes the rehabilitation procedure of the roof timber structure of a multiuse pavilion in Viseu, Portugal. The roof structure consists of a series of parallel double timber trusses, partially concealed above a polyhedral wooden plank-made ceiling. Recently, the support of one of the trusses failed and another one has been assessed as in a pre-failure condition. Some load-redistribution and the prompt shore of the structure prevented the generalized collapse. The subsequent inspection and assessment led to the conclusion that the primary cause of the collapse was the failure perpendicular to the grain of the solid timber elements inserted between the double rafters and tie-beams. The replacement of the existing with a steel structure, and the repair and reinforcement of the existing wooden trusses, were considered as intervention possibilities. The latter revealed much cheaper, less time-consuming and in line with the international recommendations on rehabilitation works, and was therefore adopted. An innovative solution, consisting of the replacement of the central timber elements in all the supports, resulted in minimum visual impact and improved the load bearing capability beyond its original value. Doi: 10.28991/cej-2020-03091628 Full Text: PDF